Electron-impact desorption of metastable particles from CO films - Shi, H.; Cloutier, P.; Sanche, L. (Физика низких температур, 1998)
The impact of monochromatic low-energy electrons (4–52 eV) is found to induce desorption of metastable particles (MP) from multilayer films formed by condensing CO gas on a Pt(111) substrate held at 20 K. The results are compared with metastable production from gaseous CO. Metastable CO (CO*) is identified as the major desorbed species, its desorption is discussed in terms of intramolecular to molecule-surface vibrational energy transfer. Primary electronic excitation proceeds via the states, a'³Σ⁺, d³Δ, e³Σ⁻, I¹Σ⁻, and D¹Δ which contribute to MP desorption directly or by first decaying in high vibrational levels of the a³Π configuration. The energy threshold of 8.0 eV for CO* desorption indicates that CO in low vibrational levels of the a³Π state does not desorb. Electronic excitation occurs either near the surface of the CO film or in the bulk. In the latter case, excitonic motion to the surface can be followed by CO* desorption.